PERAN PENDAPATAN DALAM MEMODERASI PENGARUH SIKAP PADA KESEDIAAN MEMBAYAR PRODUK RAMAH LINGKUNGAN - Komang Yogi Indra, Gunawan; Ni Wayan Sri, Suprapti (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The aim of this study is to determine the effect of attitudes toward willingness to pay of Philips LED bulb, with level  of consumer income as  moderating variable.  The study  was  conducted  in Denpasar  City with sample size of 90 LED bulbs user but have not used the Philips brand.  Sample was determined by purposive sampling and data were collected by using questionnaires distributed directly. The data were processed with Moderate Regression Analysis (MRA). The results of  this study indicate that attitudes is positively  affect willingness to pay, but the level of income is negatively affect willingness to pay. Nevertheless, income level are significantly moderate the relationship between attitude and willingness to pay, and the resultsshow a positive coefficient, which means that the income level strengthen the influence of attitude toward willingness to pay of Philips LED bulb
Keywords: attitudes, income level, willingness to pay